Substituting corn silage with reconstituted forage or nonforage fiber sources in the starter diets of Holstein calves: effects on performance, ruminal fermentation, and blood metabolites - Kargar, Shahryar (J Anim Sci, 2019)
We examined the effects of replacing corn silage (CS) with reconstituted alfalfa hay (AH) or beet pulp (BP) in the starter diet on the nutrient intake and digestibility, growth performance, rumen fermentation characteristics, selected blood metabolites, and health status in Holstein dairy calves. Newborn female calves (n = 54; 3 d of age; 39.8 ± 1.36 kg BW) were assigned randomly to 3 groups receiving starter diets containing CS [10% dry matter (DM) basis; CS diet) and reconstituted AH (10% DM, RAH diet) or BP (10% DM; RBP diet). The starter diets had the same nutrient composition and DM content. The calves were weaned on day 50 and the study continued until day 70. Nutrient intake, body weight (at weaning and at the end of the study), daily weight gain, feed efficiency, and body measurements (including heart girth, withers height, body length, body barrel, hip height, and hip width) were not affected by the diet (P > 0.05). Health-related variables including rectal temperature, fecal score, and general appearance score were not influenced by the diets (P > 0.05). During the postweaning period, apparent total tract digestibility of DM, organic matter, and crude protein were higher for RBP (P = 0.001); however, digestibility of neutral detergent fiber was lower in RAH compared with CS or RBP (P = 0.001). Daily amount of nutrient digestibility did not change across the diets (P > 0.05). Rumen fluid pH and total volatile fatty acid concentration and profile were not different across the diets after weaning (P > 0.05). Calves fed RAH or RBP had higher blood concentration of β-hydroxy butyric acid compared with CS only before weaning (P = 0.03). Blood albumin concentration was higher for RBP compared with CS or RAH during the preweaning (P = 0.006) and overall (P = 0.005) periods; however, it was lower for CS compared with RBP after weaning (P = 0.03). Concentration of other blood variables including glucose, blood urea N, total protein, and globulin did not change across the diets (P > 0.05). Calves, in general, were healthy, and replacing CS with RAH or RBP in the starter diet had no beneficial effect on their feed intake or growth performance indicating that CS and reconstituted AH or BP can be used interchangeably in dairy calf starter diets until 70 d of age, allowing dairy producers more choices in selecting the feed ingredients.